Tracheal chondrosarcoma with overlying inflammatory polyp in a dog. Issue 1 (14th March 2017) - Muller, Carrie L; Durrant, Jessica; Petrovitch, Nicholas; Shive, Heather; Scharf, Valery
Abstract : A nine‐year‐old male neutered goldendoodle was presented to the Veterinary Teaching Hospital (VTH) for further evaluation of a tracheal mass. Initially, it was evaluated by an internal medicine specialist for episodes of dyspnoea. A bronchoscopy was performed, which identified a tracheal mass. A bronchoscopic biopsy of the mass was obtained, with histopathology indicating an inflammatory polyp. The dog was then referred to the VTH for surgical excision. On presentation, a CT scan and a second bronchoscopic biopsy were performed, which revealed histological features consistent with an inflammatory polyp. Based on the patient's clinical signs and the appearance of the mass on CT, a tracheal resection and anastomosis was recommended. Histopathology of the excised mass was consistent with a tracheal chondrosarcoma that had been overlain with an inflammatory polyp. To the authors' knowledge, the following is the first report of a tracheal polyp overlying a chondrosarcoma, which was diagnosed twice as an inflammatory polyp via bronchoscopic biopsies.